Opening Speech – CLAD Congress – November 26, 2024 - Dweck, Esther (Revista del CLAD Reforma y Democracia, 2025)
It is with great satisfaction that I open the 29th Congress of the Latin American Center for Development Administration (CLAD). Created more than 50 years ago, CLAD is a strategic international organization with the mission of promoting the strengthening of institutional capacities in Ibero-American countries and the transformation of our public administrations. This mandate is more relevant today than ever before. In the first decades of this century, two major crises challenged the role of national governments: the 2008 macroeconomic crisis and the COVID-19 pandemic in 2020. The response to the former led to changes in fiscal rules in many countries, seeking greater flexibility, especially in a context of strong economic concentration. As for the latter, the State was called upon to coordinate efforts to combat the disease and mitigate its social and economic impacts. But the challenges did not stop there. In the same context, other crises have affected countries—such as the environmental and climate crisis, the rise in inequalities between individuals and nations, and the intensification of geopolitical competition—producing destabilizing global effects.